The changing role of the road traffic in the course of time - Gábor Szalkai (European Regional Science Association (ERSA), 2010)
The role of the road traffic depending on the time Gábor Szalkai, PhD. The volume of the road traffic can be observed in several European countries since the 19th century. Its role in the modal-split has many changes since that. According to this the variable of the road traffic volume has a different significance from time to time. While the horse-drawn traffic in the 19th century - parallel with the extension of the railway network - lost its original role and became dominant in the less developed regions, this process reversed in the 20th century. At the beginning the appeared engine-driven traffic connected to the population with higher social status, but in the second half of the century it became generally spread and meant the base of the regional division of labour. From this point of view it is obvious to define it as a development indicator, but its environmental effects raise questions about the sustainability of the system. My presentation is based upon this topic and focuses on the processes in Hungary.
Keywords: 330